The emergence of semantics in four linguistic traditions : Hebrew, Sanskrit, Greek, Arabic - Bekkum, Wout Jac. van. (Amsterdam ; Philadelphia : John Benjamins, 1997)
The aim of this study is a comparative analysis of the role of semantics in the linguistic theory of four grammatical traditions, Sanskrit, Hebrew, Greek, Arabic. If one compares the organization of linguistic theory in various grammatical traditions, it soon turns out that there are marked differences in the way they define the place of 'semantics' within the theory. In some traditions, semantics is formally excluded from linguistic theory, and linguists do not express any opinion as to the relationship between syntactic and semantic analysis. In other traditions, the whole basis of linguisti.
THE EMERGENCE OF SEMANTICS IN FOUR LINGUISTIC TRADITIONS; Editorial page; Title page; LCC data; PREFACE; Contents; Part One THE HEBREW TRADITION; Part Two THE SANSKRIT TRADITION; Part Three THE GREEK TRADITION; Part Four THE ARABIC TRADITION; Meaning in four linguistic traditions: a comparison; Chronological table; Index of Names; Index of Subjects; The series Studies in the History of the Language Sciences.
Includes bibliographical references (pages 323-326) and indexes.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
eBooks on EBSCOhost
Keywords: Bible. -- Criticism, interpretation, etc., Jewish; Bible. -- Critique, interprétation, etc. juives; Bible; Rabbinical literature -- History and criticism; Hebrew language -- Semantics; Sanskrit language -- Semantics; Greek language -- Semantics; Arabic language -- Semantics; Semantics, Comparative; Littérature rabbinique -- Histoire et critique; Hébreu (Langue) -- Sémantique.; Sanscrit (Langue) -- Sémantique.; Grec (Langue) -- Sémantique.; Arabe (Langue) -- Sémantique.; Sémantique comparée.; Arabic language -- Semantics; Greek language -- Semantics; Hebrew language -- Semantics; Rabbinical literature; Sanskrit language -- Semantics; Semantics, Comparative; Semantik; Semantiek; Hebreeuws; Sanskriet; Grieks; Arabisch; Sanskrit; Griechisch; Hebräisch.; Arabisch; Criticism, interpretation, etc